Doctors in Star Trek: Dr. Helen Pulasky in Star Trek: The Next Generation. (May 2020) - Grech, Victor
Abstract: Dr. Helen Pulaski served as Chief Medical Officer aboard the Starship Enterprise in the 24th century (in the second season of Star Trek: The Next Generation ). She was depicted as a grumpy and curmudgeonly character in the mould of Dr. "Bones" McCoy in the original series from the 1960s. Like all other Star Trek Doctors, her skills are legion and she is an excellent medic with a highly evolved sense of ethics.